Minimal Hepatic Encephalopathy in Patients with Cirrhosis Using Psychometric Hepatic Encephalopathy Score Tests: Minimal Hepatic Encephalopathy with Psychometric Hepatic Encephalopathy Score - Zakir, Humaira; Khokar, Amanullah; Manzoor, Waqas; Aman, Habiba; Waqar, Mariam Fatima; Majid, Abdul; Khan, Hina (Pakistan Journal of Health Sciences, 2025)
Minimal hepatic encephalopathy (MHE) is defined as changes in cognitive ability, electrophysiology, and homeostasis of neurotransmission and blood flow in the cerebrum. It is observed in patients with chronic liver disease and cirrhosis who do not have clinical features of overt hepatic encephalopathy. The International Society for Hepatic Encephalopathy and Nitrogen recommend the Psychometric Hepatic Encephalopathy Score (PHES) to easily detect and treat these patients. Objectives: To calculate the frequency of MHE amongst patients with cirrhosis of the liver based on the Psychometric Hepatic Encephalopathy Score. Methods: This cross-sectional study was conducted at the Department of Medicine, Al Tibri Medical College, Karachi. A total of 235 patients with cirrhosis of the liver with normal mental status were included. Patients were given 5 printed sheets of paper, one each for the number connection test A and test B, line tracing, serial dotting test and digit symbol test. A score of two or less was labelled as minimal hepatic Encephalopathy. Chi-square test was applied for checking the association, and a p-value≤0.05 was considered significant. Results: There were 62.13% male and 37.87% female. The mean age was 45.47 ± 13.28 years. The mean duration of cirrhosis was 5.54 ± 3.7 years. Most of the patients (53.6%) successfully performed four and five PHES tests, while 22.13% patients successfully performed three tests. 15.32% and 8.94% were successfully performed two and one PHES test, respectively. Minimal hepatic encephalopathy was observed in 24.68% cases. Conclusions: It was concluded that the PHES is easily detected and can treat minimal hepatic encephalopathy.